Valerianaceae endémicas del Perú - León, Blanca (2006)
The Valerianaceae are represented in Peru by six genera and 92 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly herbs and subshrubs. Here we recognize 41 species and two varieties as endemics, in five genera. Valeriana is the genus with more endemic species. These taxa are found mainly in Humid and Dry Puna, Mesoandean and High- Andean regions, between 2700 and 5200 m elevation. We apply IUCN categories and criteria to 16 endemics. Apparently, 14 endemic taxa have been recorded within Peru’s protected areas system.